ANALISIS PENGARUH PEMBELAJARAN DARING TERHADAP PRESTASI BELAJAR SISWA DIMASA PANDEMI COVID-19 MENGGUNAKAN MODEL REGRESI BERGANDA (STUDI KASUS DI SMPN 33 BANJARMASIN) - Muhammad Yusril Widodo; Nur Salam; Aprida Siska Lestia (RAGAM: Journal of Statistics & Its Application, 2023)
The impact of the Covid-19 pandemic that occurred from 2019-2021 has had an impact on many sectors, one of which is the education sector. With this pandemic, learning takes place online which is possible for junior high school students is not an effective thing so that it has an impact on the final grades of student learning. This study aims to estimate the parameters of the multiple linear regression model formed in the analysis of the effect of online learning on student achievement at SMPN 33 Banjarmasin during the Covid-19 pandemic, and to explain the factors that significantly influence student achievement at SMPN 33 Banjarmasin during the pandemic. Covid-19. This study uses the independent variables of learning media and teacher teaching methods while the dependent variable uses student achievement. The population of this research is students at SMPN 33 Banjarmasin with a total sample of 120 respondents. Analysis was performed using multiple linear regression analysis. The results of the study showed that there was a significant influence between learning media and teacher teaching methods on student achievement at SMPN 33 Banjarmasin during the Covid-19 pandemic. Other results are shown based on testing the hypothesis that the variable that has the most influence is the teacher's teaching method variable. The teacher's teaching method variable (X2) has the largest relative contribution compared to the learning media variable (X1). Keywords: Online Learning, Learning Achievement, Multiple Linear Regression